Selective coordination for overcurrent protective devices: applications for buildings in the United States - Harvey, Tasha (Kansas State University, 2012)
The inclusion of Selective Coordination in the NEC since the 2002 revision and the expansion of applications for which coordination of Over-current Protective Devices is required have resulted changes in design approaches for electrical engineers. In order to meet the requirements of the NEC regarding Selective Coordination for secondary power systems within buildings, often, upstream protective devices need to be held-in to a short-circuit condition, thus increasing the Arc Flash Energy. Electrical engineers must understand the many aspects of Selective Coordination when approaching a project from the very beginning. Decisions made by the engineer regarding Selective Coordination will have influence on project cost, project timeline, robustness of the electrical equipment, and safety of personnel working near or on the electrical equipment. The main objectives of this report are to convey an understanding of the following: recent changes in requirements for Selective Coordination, implications of short-circuit analysis, impacts of selectively coordinated systems on Arc Flash Energy, risks surrounding Arc Flash Hazards, and design processes regarding Selective Coordination.
Keywords: Selective coordination; Overcurrent protective device; Building; Circuit breaker; Fuse; Electrical distribution; Architectural engineering (0462); Architecture (0729); Engineering (0537)